Does Habitat Management for Northern Bobwhites Benefit the Red Imported Fire Ant? - A.R. Forbes; C. B. Dabbert; R. B. Mitchell; J. M. Mueller (National Quail Symposium Proceedings, 2017)
Red imported fire ants (Solenopsis invicta) have caused damage to agricultural, economic, and wildlife resources since their accidental introduction. Previous studies have suggested that red imported fire ant (RIFA) mound densities are positively correlated to habitats maintained through disturbance. Prescribed burning and disking are two techniques commonly used to disturb portions of the landscape to maintain early successional habitats for northern bobwhite (Colinus virginianus). We tested the hypothesis that prescribed burning and disking would increase RIFA mound densities. This study was conducted in Refugio County, Texas in the Texas Coastal Prairie on Loamy Prairie range sites. Red imported fire ant mound densities were different between years (F = 5.05, df = 2, P = 0.0148). However, burning and disking had no impact (F = 0.22, df = 2, P = 0.8044) on RIFA mound densities. Initially high RIFA mound densities in our study area coupled with the territoriality of predominantly monogyne (single-queen) colonies may have limited increases in RIFA mound density in response to treatments on these study sites.
Keywords: biological control; burning; Colinus virginianus; disking northern bobwhite; red imported fire ants; Solenopsis invicta